1983
DOI: 10.1002/cne.902200303
|View full text |Cite
|
Sign up to set email alerts
|

Afferent projections to the oral motor nuclei in the rat

Abstract: Projections to the trigeminal, facial, ambiguus, and hypoglossal motor nuclei were determined by using horseradish peroxidase histochemistry. Most of the afferent projections to these motor nuclei were from the brainstem reticular formation, frequently in areas adjacent to other synergetic motor nuclei. The reticular formation lateral to the hypoglossal nucleus and reticular structures surrounding the trigeminal motor nucleus projected to each of these other brainstem motor nuclei involved in oral-facial funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
236
4
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 454 publications
(279 citation statements)
references
References 68 publications
38
236
4
1
Order By: Relevance
“…For example, brainstem innervation arises from the red nucleus, mesencephalic tegmentum, olivary pretectal nucleus, dorsolateral pontine tegmentum, principle trigeminal nucleus, ventrolateral pontine tegmentum and medullary tegmentum (Travers and Norgren, 1983;Holstege et al, 1984;Holstege et al, 1986;Isokawa-Akesson and Komisaruk, 1987). Additional studies have shown that several regions of the cerebral cortex directly innervate the intermediate subnucleus, including the face region of the primary motor cortex, lateral premotor cortex, supplementary motor cortex, rostral cingulate motor cortex and caudal cingulate motor cortex (Kuypers, 1958;Jenny and Saper, 1987;Morecraft et al, 2001;Gong et al, 2005).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 99%
“…For example, brainstem innervation arises from the red nucleus, mesencephalic tegmentum, olivary pretectal nucleus, dorsolateral pontine tegmentum, principle trigeminal nucleus, ventrolateral pontine tegmentum and medullary tegmentum (Travers and Norgren, 1983;Holstege et al, 1984;Holstege et al, 1986;Isokawa-Akesson and Komisaruk, 1987). Additional studies have shown that several regions of the cerebral cortex directly innervate the intermediate subnucleus, including the face region of the primary motor cortex, lateral premotor cortex, supplementary motor cortex, rostral cingulate motor cortex and caudal cingulate motor cortex (Kuypers, 1958;Jenny and Saper, 1987;Morecraft et al, 2001;Gong et al, 2005).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 99%
“…Although we have used a relative small number of animals, in all cases, the pattern of retrograde-labeled neuron distribution was similar. In concordance with previous results [32], we observed retrograde-labeled neurons in a variety of brainstem areas such as the mesencephalic trigeminal nucleus (Me5), the principal trigeminal nucleus (Pr5), the spinal trigeminal oral and interpolar subnuclei (Sp5O and Sp5I), the supratrigeminal nucleus (Su5), the contralateral Mo5, the juxtatrigeminal and intertrigeminal nuclei, the nucleus reticular pontine caudal (nPC), the gigantocellular nucleus (GI) and GI pars ␣ (GI␣), the parvicellular reticular formation pars ␣ (PCRt␣), the raphe pallidus and obscurus nuclei (RPa and ROb), and the nucleus of the solitary tract (NTS). In addition, we found moderate numbers of retrograde-labeled neurons in the central nucleus of the amygdala (CeA), and in the parasubthalamic nucleus (PSTh) ( Table 1 and Fig.…”
Section: Conclusãosupporting
confidence: 82%
“…These neurons project to the Mo5, as observed by others [20] and confirmed in the present study. Moreover, according to other studies [13,20,32], except in the caudal spinal trigeminal nucleus, retrograde-labeled neurons have been found throughout the trigeminal complex nuclei. The trigeminal sensory nuclei (Me5 and Pr5) may integrate sensory information used for maintenance of masticatory rhythm, which is generated in the reticular formation [25,33].…”
Section: Conclusãomentioning
confidence: 99%
See 2 more Smart Citations